Collapse Analysis of Car Porch Steel Structure due Wind Storm - T. A., Majid; S. S., Zaini; Noram Irwan, Ramli (Penerbit UMP, 2011)
Malaysia is a country with tropical climate. During the monsoon season, heavy rains and thunderstorm affect many places, especially at the east coast of Peninsular Malaysia and East Malaysia. Strong wind that produced significant wind force has proven to cause damage especially to low-rise non-engineered structures. Currently, numerous evidences of damages and loss caused by thunderstorm can be obtained. In 30st July 2009, a car porch steel frame in Taman Murni, Parit Buntar, Perak, was badly damaged during a heavy down fall and strong wind. An investigation had been carried out. From the result it show that the actual steel frame at the site was tremendously under designed which reflect the non-involvement of structural engineers.